Applying Integrating Testing of Microservices in Airline Ticketing System - Dearisma Arfinda Ma'ruf; Selo Sulistyo; Lukito Edi Nugroho (IJITEE (International Journal of Information Technology and Electrical Engineering), 2020)
Microservices have been applied on several major systems including airlines. The characteristics of microservices which are independent and also interconnected need to be tested. The testing is done to preserve the system’s sequential stage processes, especially the online ticket reservation. Four features which are the search, booking, payment, and booking info feature are tested. This research performed three stages of testing on the microservices, those are unit testing, integrity testing, and end-to-end testing. Unit testing was conducted to test every function on every nodule, integrity testing was done to test interconnection between microservices, and end-to-end testing was to test the final results obtained after the unit test and integrity test were carried out. The three stages of testing must be done sequentially. The system on the airline provides the valid or correct response. Three stages of testing can be applied on other airlines by obtaining a legal API and can be accessed publicly.